Study of neutron moderation properties of liquid moderators in room and cryogenics temperature. Issue 1 (April 2020) - Azmi, Danial Zikri; Yahya, Mohd-Syukri; Hamid, Nasri A.; Idris, Faridah Mohamad; Murshidi, Julie Adrianny; Azman, Azraf; Mohamed, Abdul Aziz
Abstract: Neutron moderation is crucial to sustain the chain reactions in a nuclear fission reactor. To understand further basic characteristics of neutron moderation, this research investigated fundamental moderating properties of liquid moderators typically used in modern power reactors, namely water and salt solution. Specifically, we employed a small angle neutron scattering (SANS) technique at beam-port number 4 of Malaysia's PUSPATI TRIGA Reactor to study moderating characteristics of the liquid moderators at both room and cryogenic temperatures. To achieve cryogenic temperatures, a leakage-proof liquid sample holder was placed in a cryostat cooled by liquid nitrogen. Moderated and unmoderated neutron spectra were collected using Microspec-6 for analysis, which clearly shows that peak neutron counts dropped at cryogenic from room temperatures.